Assessing Smoothness of Arm Movements With Jerk: A Comparison of Laterality, Contraction Mode and Plane of Elevation. A Pilot Study - Roren, Alexandra; Mazarguil, Antoine; Vaquero-Ramos, Diego; Deloose, Jean-Baptiste; Vidal, Pierre-Paul; Nguyen, Christelle; Rannou, François; Wang, Danping; Oudre, Laurent; Lefèvre-Colau, Marie-Martine (Frontiers in Bioengineering and Biotechnology, 2022)
Measuring the quality of movement is a need and a challenge for clinicians. Jerk, defined as the quantity of acceleration variation, is a kinematic parameter used to assess the smoothness of movement. We aimed to assess and compare jerk metrics in asymptomatic participants for 3 important movement characteristics that are considered by clinicians during shoulder examination: dominant and non-dominant side, concentric and eccentric contraction mode, and arm elevation plane. In this pilot study, we measured jerk metrics by using inertial measurement units for 11 different active arm movements (ascending and lowering phases): 3 bilateral maximal arm elevations in sagittal, scapular and frontal plane; 2 unilateral functional movements (hair combing and low back washing); and 2 unilateral maximal arm elevations in sagittal and scapular plane. Unilateral movements were performed with both arms alternately, right arm first. Each arm movement was repeated 3 times successively and the whole procedure was performed 3 times on different days. The recorded time series was segmented with semi-supervised algorithms. Comparisons involved the Wilcoxon signed rank test (p<0.05) with Bonferroni correction. We included 30 right-handed asymptomatic individuals (17 men, mean [SD] age 31.9 [11.4] years). Right jerk was significantly less than left jerk for bilateral and unilateral arm elevations in all planes (all p≤6.30x10-3) and for functional movement (p≤1.47×10−2). Jerk was significantly reduced during the concentric (ascending) phase than eccentric (lowering) phase for bilateral and unilateral right and left arm elevations in all planes (all p≤2.12×10−2). Jerk during bilateral arm elevation was significantly reduced in the sagittal and scapular planes versus the frontal plane (p=4.67×10−2 and p=6.48×10−9, respectively) and in the sagittal versus scapular plane (p=2.60×10−2). Jerk during unilateral left arm elevation was significantly reduced in the sagittal versus scapular plane (p=3.73×10−2). Jerk metrics did not differ between sagittal and scapular unilateral right arm elevation. Using inertial measurement units, jerk metrics can well describe differences beween the dominant and non-dominant arm, concentric and eccentric modes and planes in arm elevation. Jerk metrics were reduced during arm movements performed with the dominant right arm during the concentric phase and in the sagittal plane.